The Relationship between Structured Health Education About Breastfeeding Against Exclusive Breastfeeding Status - Hasriantirisna, Hasriantirisna (Advances in Healthcare Research, 2023)
Purpose: This study investigates the relationship between structured health education and exclusive breastfeeding (EBF) status, aiming to understand how tailored educational interventions can enhance the initiation and sustainability of EBF for the recommended six months. Research Design and Methodology: The study employs a qualitative systematic literature review (SLR) approach, analyzing peer-reviewed journal articles, conference papers, and relevant academic publications. The literature spans from 2010 to 2024, focusing on structured health education, digital health interventions, and their impact on EBF practices. Findings and Discussion: The findings indicate that structured health education, particularly when culturally sensitive and supported by digital tools such as mobile health (mHealth) applications, significantly improves EBF outcomes. The study highlights the importance of continuous support through follow-up sessions and peer groups. Additionally, it underscores the role of workplace policies and public health infrastructure in sustaining breastfeeding practices. The results align with the Health Belief Model and the Theory of Planned Behavior, demonstrating that well-structured education can effectively promote health behaviors. Implications: This research contributes to both scientific knowledge and practical application by emphasizing the integration of digital tools and supportive policies in health education. The study's originality lies in its comprehensive approach, offering valuable insights for healthcare providers and policymakers to enhance maternal and child health outcomes globally.